Music as Labour: Inequalities and Activism in the Past and Present - Abfalter, Dagmar; Reitsamer, Rosa (Taylor & Francis, 2022)
This book brings together research at the intersection of music, cultural industries, management, antiracist politics and gender studies to analyse music as labour, in particular highlighting social inequalities and activism. Providing insights into labour processes and practices, the authors investigate the changing role of manifold actors, institutions and technologies and the corresponding shifts in the valuation and evaluation of music achievements that have shaped the relationship between music, labour, the economy and politics. With research into a variety of geographic regions, chapters shed light on the various ways by which musicians’ work is performed, constructed and managed at different times and show that musicians’ working practices have been marked by precarity, insecurity and short-term contracts long before capitalism invited everybody to ‘be creative’. In doing so, they specifically examine the dynamics in music professions and educational institutions, as well as gatekeepers and mechanisms of inclusion and exclusion. With a specific emphasis on inequalities in the music industries, this book will be essential reading for scholars seeking to understand the collective actions and initiatives that foster participation, inclusion, diversity and fair pay amongst musicians and other workers.
Accepted: 2022-05-18T09:38:24Z
Keywords: Music; Myriam; Personnel and human resources management; bic Book Industry Communication::A The arts::AV Music; bic Book Industry Communication::K Economics; business & management::KJ Business & management::KJM Management & management techniques::KJMV Management of specific areas::KJMV2 Personnel & human resources management; finance

In Her Own Words: Documenting the Current Realities of Women-in-Jazz - Manfredo, Alexandra, Kiernan Steiner (The Routledge Companion to Jazz and Gender, 2022)
Since the inception of jazz, the lives and experiences of women-in-jazz have been inadequately documented and archived, which has led to a lack of female representation in the jazz community. During the recent resurgence of the #MeToo Movement, many women-in-jazz bravely shared stories of sexual discrimination and harassment. As the jazz community continues to address the gender disparity, women’s stories need to be centered in order to address current realities of women-in-jazz. By documenting the experiences of women-in-jazz in higher education as students, educators and performers, sexual discrimination and harassment must be considered as contributing factors of the gender disparity in jazz.
Num Pages: 14
Keywords: Jazz; Music; Myriam

Raising Their Voices: Independent Review into Sexual Harm, Sexual Harassment, and Systemic Discrimination in the National Music Industry - Shehadie, Alexandra; The Review Team (Support Act, 2022)
Keywords: Bibliographie; Nettoyer